Efektivitas regulasi pengelolaan sampah plastik di indonesia: Sebuah studi literatur - Wahyuni, Dessy Dwi (Maliki Interdisciplinary Journal, 2025)
Plastic waste has become a pressing environmental issue in Indonesia as the production and consumption of single-use plastics continue to increase. The government has introduced several regulations, such as Law No. 18/2008 on Waste Management, Presidential Regulation No. 83/2018 on Marine Debris Management, and local government policies banning single-use plastic bags. While these regulations indicate the state’s commitment to addressing the plastic waste crisis, their effectiveness remains questionable. This literature review analyzes various studies, reports, and policy documents on plastic waste management in Indonesia, focusing on the challenges, achievements, and obstacles in implementing regulations. The findings show that the effectiveness of regulations is still limited due to weak law enforcement, inadequate waste management infrastructure, and low public awareness. This study emphasizes the need for continuous evaluation, stronger stakeholder collaboration, and policy innovation based on the circular economy as a long-term solution.